Economic Value of Solid Waste for Improved Solid Waste Management in Nandi County, Kenya - James Meli; Sumukwo Joel; Kiplimo Lagat (African Journal of Education,Science and Technology (AJEST), 2025)
Due to rapid population growth and urbanization Nandi County is experiencing challenges of managing urban solid waste especially as this is an economic commodity that may not be optimally allocated through the normal market mechanism system. This is because supply-side management practices have failed and hence there is need for demand-oriented approach. The objectives of this study include; assessing the WTP for improved management of solid waste; evaluate potential income opportunities in managing waste; and provide policy implications. The study used a sample size of 380 households through stratified sampling procedures. Interview guides and questionnaires were used in data collection. Results show that only 27% of individual residents and 18% of corporate organizations paid for these services while the rest (73% and 82% respectively) cannot internalize environmental degradation. High income households expressed the highest willingness to pay (WTP) of 60%. On average respondents WTP is KSh. 300 monthly for improved services, while corporates had WTP of KSh. 1,000. Regression analysis showed that gender, education level, and household income were significant predictors of WTP. The study concluded that gender, education level, and household monthly income significantly influence individuals’ willingness to pay for improved solid waste management in Nandi County. It recommends strengthening regulations to enforce proper waste disposal and introduce equitable tariff structures. Expanding participation through affordable rates will help achieve economies of scale, ensuring sustainable financing for waste management services.